2014
DOI: 10.1183/09031936.00041914
|View full text |Cite
|
Sign up to set email alerts
|

Viral, bacterial or both? Regardless, we need to treat infection in COPD

Abstract: @ERSpublications Specific prevention of infective exacerbations of COPD is required http://ow.ly/vdIIh Guidelines indicate that pharmacological treatment of chronic obstructive pulmonary disease (COPD) is based on bronchodilators with the addition of inhaled corticosteroids (ICS) in frequent exacerbators [1]. Although this recommendation is in accordance with the best evidence available, it does not take into account that more than half of the exacerbations are infective and infections are not adequately preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
(38 reference statements)
0
11
1
Order By: Relevance
“…Although previous studies have demonstrated more severe respiratory symptoms, prolonged recovery times and higher levels of serum interleukin-6 levels in patients with virus-induced exacerbation compared to non-virus-induced exacerbations [9,26], our study is the first to show that CRP levels are strongly associated with viral rather than bacterial detection. Several other studies have examined CRP levels in § : despite a p-value of <0.1 on univariate analysis, this variable could not be added to the multivariate models due to the small number of outcomes (i.e.…”
Section: Discussioncontrasting
confidence: 67%
“…Although previous studies have demonstrated more severe respiratory symptoms, prolonged recovery times and higher levels of serum interleukin-6 levels in patients with virus-induced exacerbation compared to non-virus-induced exacerbations [9,26], our study is the first to show that CRP levels are strongly associated with viral rather than bacterial detection. Several other studies have examined CRP levels in § : despite a p-value of <0.1 on univariate analysis, this variable could not be added to the multivariate models due to the small number of outcomes (i.e.…”
Section: Discussioncontrasting
confidence: 67%
“…Therefore, whilst the present analysis has reaffirmed both the strong relationship between disease severity and exacerbation frequency, and the importance of dyspnoea in COPD patients, it appears that the intensity of other stable state symptoms is not a key driver of exacerbation symptom severity. This may be because exacerbation severity is largely driven by exacerbation triggers such as respiratory viruses and bacteria [37].…”
Section: Discussionmentioning
confidence: 99%
“…There is enough evidence to suggest that a change in bacterial strain is associated with the initiation of an exacerbation, and that viral infection is associated with exacerbation and subsequent bacterial infection. It is possible that viral infection can lead to an infection by a new bacterial strain and both mechanisms could coexist in a given patient, but apparently both can initiate an exacerbation by themselves [6].…”
Section: Key Pointsmentioning
confidence: 99%
“…These bacteria contribute to chronic airway inflammation leading to COPD progression [2,4,5] and may be associated with exacerbations when they increase in concentrations in the airways, when there is a change in these strains or after a viral respiratory infection. These different mechanisms may be responsible for the development of a bacterial exacerbation of COPD [6].…”
Section: Introductionmentioning
confidence: 99%